Reserving the right to torture - Blakeley, Ruth (Contesting torture, 2023)
The United States, United Kingdom, and other liberal democracies are signatories to the Convention Against Torture. Yet liberal democracies have their own dark histories of complicity in torture. Following revelations of CIA and US military torture post 9/11, and of collusion by UK intelligence services, pressure mounted for a public inquiry in the United Kingdom. The Intelligence and Security Committee (ISC) Inquiry was ostensibly aimed at accountability. Key findings were that: British collusion was far more extensive than previously known; there are considerable weaknesses in training guidance and policy; and there is little political will to address these matters. This chapter explores the weaknesses in training, guidance, policy, and accountability, and will argue that these arise from a long history of attempting to carve out spaces in which certain actors are exempted from the anti-torture norm. Counterintuitively, this is achieved partly because of the UK's self-appointed role as champion of human rights elsewhere.